Erlotinib in salvage treatment of patients with advanced non-small cell lung cancer: results of an expanded access programme in Poland - Kowalski, Dariusz M.; Krzakowski, Maciej; Ramlau, Rodryg; Jaskiewicz, Piotr; Janowicz-Żebrowska, Anna (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : Erlotinib and gefitinib are reversible EGFR-TKI administered orally. Results of the phase III study JBR.21 proved the clinical efficacy of erlotinib-based regimens as second- or third-line treatment of advanced NSCLC. We analyze efficacy of treatment with erlotinib in patients suffering from advanced stage NSCLC who participated in the multicentre, international phase IV study – MO 18109 TRUST (expanded access clinical program of TarcevaTM in patients with advanced stage IIIB/IV NSCLC). Our analysis was performed based on clinical data derived from centres with the largest number of patients who received erlotinib. Material and methods : Between May and November 2005, a total of 56 patients (19 women and 37 men) with histologic or cytologic diagnosis of NSCLC were included in the study. The histological diagnosis was: squamous-cell (n = 23), adenocarcinoma (n = 20), broncho-alveolar carcinoma (n = 2). In 11 patients the type of NSCLC was not specified. Results: Patients received erlotinib in a single dose of 150 mg per day. Partial response (PR), stable disease (SD) or progressive disease (PD) were observ-ed in 5 (9%), 33 (59%) and 16 (29%) patients respectively. Median PFS was 16.0 weeks. In the study population adverse events (AE) were noted in 12 (21%) patients. Conclusions : Results of the TRUST study in the Polish population confirmed the efficacy of erlotinib in advanced NSCLC after failure of prior platinum-based chemotherapy. Treatment with erlotinib was associated with longer PFS as compared to the JBR.2 study, whole TRUST study population and Italian population included in the TRUST study.